2016
DOI: 10.1007/s10461-016-1493-8
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Factors as Correlates and Predictors of High Depressive Symptoms Among Black Men Who Have Sex with Men in HPTN 061

Abstract: Depression is linked to a range of poor HIV-related health outcomes. Minorities and men who have sex with men (MSM), suffer from high rates of depression. The current study examined the relationship between depressive symptoms and social network characteristics among community-recruited Black MSM in HPTN 061 from 6 US cities. A social network inventory was administer at baseline and depression was assessed with the CES-D at baseline, 6, and 12-months. At baseline, which included 1167 HIV negative and 348 HIV p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Importantly, for patients with depressive symptoms, social capital was a protective factor – the detrimental effect of depressive symptoms on viral suppression was worse for those with low social capital. These results were consistent with our theoretical expectations, and with several other studies that examined related study questions in similar populations (46, 47).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Importantly, for patients with depressive symptoms, social capital was a protective factor – the detrimental effect of depressive symptoms on viral suppression was worse for those with low social capital. These results were consistent with our theoretical expectations, and with several other studies that examined related study questions in similar populations (46, 47).…”
Section: Discussionsupporting
confidence: 93%
“…The function of social capital as a buffer against depressive symptoms is consistent with a prior US study that found social network factors (including size of emotional, financial and medical support networks) to be significantly associated with fewer depressive symptoms in a mixed-serostatus sample of Black men who have sex with men (MSM) participating in the HIV Prevention Trials Network (HPTN) 061 protocol (46). Although this study did not label their predictor variables as social capital per se , the size of networks and different support functions described by the authors align well with specific items in our measure (e.g., items assessing network size and items assessing the presence of specific assets such as “medical or health knowledge”, “large wealth”, etc.)…”
Section: Discussionsupporting
confidence: 80%
“…In the same vein, a longitudinal analysis in Taiwan recognized that participation in religious movements or secular activities organized by religious institutions promoted an improvement in mental health and reduced symptoms of depression [ 32 ]. Recent empirical works on suicide [ 34 , 35 ] show that greater social support and attachments are related to fewer depression symptoms and other mental health issues among very diverse populations. Improvement in the feeling of belonging and promotion of interactions and social cohesion among those who profess religious beliefs suggests a lower percentage of depression, suicide attempts, and feelings of anguish and a higher level of wellbeing [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…[social participation]). Network members could provide multiple forms of support, which were classified as "personal/emotional", "medical", "financial", and "social participation" support based on the aforementioned social network member criteria and past literature [25].…”
Section: Study Analysismentioning
confidence: 99%